(untitled) (Research Nepal Journal of Development Studies, 2025)
It is brought together in this volume invite a necessary pause in Nepal’s ongoing development discourse. Gandhian Tourism: Quantifying Economic Leakage and Carbon Equity in Nepal, Indicators of Development Economics: A Critical Analysis, Tourism Cooperatives of Nepal: Challenges and Opportunities, Deconstructing Development: Postmodern Analysis of Socializing National Cinema in Nepal, and Government Expenditure in Urban Development in Comparison to Development Budget in Nepal collectively challenge the intellectual comfort of dominant development frameworks. They remind us that the language of GDP growth, budget expansion, and infrastructural progress. It often conceals deeper fractures: unequal distribution, ecological imbalance, and the erosion of cultural contexts. In extending this critique, Assessing Knowledge and Practices of Farmers on Climate Change Adaptation in Panchkhal Municipality-3, Kavrepalanchok, Nepal and Shaping Nepal’s Development from Belt and Road Initiative Project: Geopolitical Dynamics situate Nepal within a broader environmental and geopolitical landscape, where local vulnerabilities intersect with global ambitions and strategic dependencies. It does not remain confined to critique alone; it turns our attention toward the lived realities that ultimately define development. Changing Role of Tamang Women at Household Level in Mahalaxmi Municipality-10, Lalitpur, Nepal, From Grants to Loans: Nepal’s Shifting Aid Architecture and Its Macroeconomic Implications, Environmental Health Treatment in Nepal: A Study of Money Borrowing and Asset Sales for Individual Households, and Socioeconomic Effect of Remittance on Household Economy in Nepal illuminate the everyday negotiations of households as they navigate shifting economic structures and social expectations. These studies reveal a paradox at the heart of development progress that empowers can also marginalize; growth that uplifts can simultaneously deepen vulnerability. We see this volume not merely as a collection of academic inquiries, but as a call for a more reflective, humane, and contextually grounded approach to development, one that harmonizes economic ambition with social justice, environmental responsibility, and the preservation of Nepal’s diverse cultural fabric.